Pengawalan Lalu Lintas Pada Kerja Menaiktaraf Infrastruktur Jalan Raya - Goh, Kai Chen; Kaderan, Siti Norsyafinaz; Mohamed, Sulzakimin; Omar, Roshartini; Shafii, Haryati (Research in Management of Technology and Business, 2023)
The increase in population in an area will show an increase in the built road infrastructure. Roads are an important network to connect an individual from one destination to another. As the population continues to increase, it will contribute to traffic congestion where the road is heavily used by working users and so on and will also cause the road to suffer damage such as cracking, sagging and so on. With that, road upgrading works will be carried out to overcome the damage problem. However, when doing these upgrading works can also lead to risks such as accidents due to unsystematic management. There are three objectives of the study carried out by the researcher, namely to identify the traffic control methods implemented, to identify the problems faced by the contractor for traffic control during the work of upgrading the road infrastructure and to suggest improvements for traffic control. This study focuses on upgrading the road infrastructure around the Batu Pahat district. The method used for this study is a quantitative method which is through the distribution of questionnaires to identify the traffic control methods implemented, identify the problems faced by contractors for traffic control during the work of upgrading the road infrastructure and suggest improvements for the current traffic control road upgrading work. The respondents involved are G2 grade contractors and a total of 43 respondents have been involved in this study. The findings of the study found that all respondents agreed on the first objective which is the traffic control method carried out, while, for the second objective, the problem of traffic flow became the main problem faced by contractors when upgrading roads. As for suggestions for improving traffic control, it is to put safety signs, install ’blinkers’ lights, safety barrier walls. The results of this study shows that the correct traffic control methods can reduce the risk to road users.